Comparison of the Technique of the Football Quarterback Pass Between High School and University Athletes. Issue 9 (September 2018) - Toffan, Adam; Alexander, Marion J.L.; Peeler, Jason
Abstract : Abstract: Toffan, A, Alexander, MJL, and Peeler, J. Comparison of the technique of the football quarterback pass between high school and university athletes. J Strength Cond Res 32(9): 2474–2497, 2018—The purpose of the study was to compare the most effective joint movements, segment velocities, and body positions to perform the fastest and most accurate pass of high school and university football quarterbacks. Secondary purposes were to develop a quarterback throwing test to assess skill level, to determine which kinematic variables were different between high school and university athletes, and to determine which variables were significant predictors of quarterback throwing test performance. Ten high school and 10 university athletes were filmed for the study, performing 9 passes at a target and 2 passes for maximum distance. Thirty variables were measured using Dartfish Team Pro 4.5.2 video analysis system, and Microsoft Excel was used for statistical analyses. University athletes scored slightly higher than the high school athletes on the throwing test; however, this result was not statistically significant. Correlation analysis and forward stepwise multiple regression analysis were performed on both the high school players and the university players to determine which variables were significant predictors of throwing test score. Ball velocity was determined to have the strongest predictive effect on throwing test score ( r = 0.900) for the high school athletes; however, position of the back foot at release was also determined to be important ( r = 0.661) for the university group. Several significant differences in throwing technique between groups were noted during the pass; however, body position at release showed the greatest differences between the 2 groups. High school players could benefit from more complete weight transfer and decreased throw time to increase throwing test score. University athletes could benefit from increased throw time and greater range of motion in external shoulder rotation and trunk rotation to increase their throwing test score. Coaches and practitioners will be able to use the findings of this research to help improve these and related throwing variables in their high school and university quarterbacks.